2013
DOI: 10.1111/jgs.12553
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing Dysfunction and Autonomic Nervous System Dysfunction in Alzheimer's Disease: A Scoping Review of the Evidence

Abstract: Current evidence indicates that swallowing impairment, as well as ANS dysfunction, may occur in AD. Potential relationships between dysphagia and ANS dysfunction in AD have not been examined. Future research should explore the possibility that swallowing and ANS dysfunction in AD are related.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
1
15

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(89 citation statements)
references
References 45 publications
(222 reference statements)
4
69
1
15
Order By: Relevance
“…Such pneumonic changes are also described in human patients with neurodegenerative disorders like Parkinson's or Alzheimer's disease or stroke. It was supposed that aspiration pneumonia of these patients was the result of swallowing disturbances, which may be due to autonomic nervous system dysfunction (Kim et al 2000;Affoo et al 2013;Cereda et al 2014). This feature seems to be of special interest for the present study because dt-MP mice showed widespread neurodegenerative lesions in the brain stem, including nuclei important for the oral and pharyngeal phase of the swallowing process, namely the trigeminal nuclei and the pontine reticular formation (Lang 2009).…”
Section: Discussionmentioning
confidence: 92%
“…Such pneumonic changes are also described in human patients with neurodegenerative disorders like Parkinson's or Alzheimer's disease or stroke. It was supposed that aspiration pneumonia of these patients was the result of swallowing disturbances, which may be due to autonomic nervous system dysfunction (Kim et al 2000;Affoo et al 2013;Cereda et al 2014). This feature seems to be of special interest for the present study because dt-MP mice showed widespread neurodegenerative lesions in the brain stem, including nuclei important for the oral and pharyngeal phase of the swallowing process, namely the trigeminal nuclei and the pontine reticular formation (Lang 2009).…”
Section: Discussionmentioning
confidence: 92%
“…Scoping reviews are literary searches that are used to provide a preliminary assessment of the size and scope of a body of literature as well as identify strengths, weaknesses and gaps in the research 18 19. Scoping reviews have been used to summarise bodies of literature on concussion rehabilitation strategies20 and on other health-related issues like Alzheimer's disease,21 HIV rehabilitation22 and in settings such as trauma centres23 and intensive care facilities 24. Because research on concussion education programmes is relatively new, a scoping review is ideal to determine the state of these education programmes.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, no existe un consenso en cuanto a su idoneidad de uso según el caso (2). Un test que sí se ha demostrado útil en la clínica es el método de exploración clínica Volumen-Viscosidad (MECV-V) (1,4,11,23,29,33,36,37), empleado para detectar las posibles aspiraciones silentes y basado en la observación de las reacciones de tos, asfixia y alteración de voz (32,37) (Fig.…”
Section: Diagnóstico De La Disfagia Y Prevención De Complicacionesunclassified
“…Es un proceso neuromuscular complejo, requiere coordinación muy precisa e implica una secuencia de acontecimientos que permiten la progresión del bolo, transportándolo desde la vía aérea (1). El objetivo de la deglución es la nutrición del individuo, teniendo dos características fundamentales: la eficacia de la deglución, refiriéndose a la posibilidad de ingerir la totalidad de las calorías y el agua necesarios para mantener una adecuada nutrición e hidratación; y la seguridad de la deglución, siendo esta la posibilidad de ingerir el agua y las calorías necesarias sin que se produzcan complicaciones respiratorias (2).…”
Section: Introductionunclassified
See 1 more Smart Citation